Primatology - Rosenberger, Alfred L., author.
1 online resource
Keywords: "This book is an accessible and comprehensive introduction to primatology. It provides both a survey and synthesis of primate history, biology and behavior. As a survey, it offers a focused review of living and extinct primates in regional and community frameworks. As a synthesis, it applies the community perspective in a unique way to explore primates' adaptive diversity in the context of how evolution works. The book encourages students to study primates as integrated members of regional communities, ecologically, historically and evolutionarily. The chapters are organized to emphasize the patterns of primate radiations in the four regions of the world where primates live, and to facilitate comparisons among the radiations. The overviews of communities illustrate how the ecological adaptations of different species and taxonomic or phylogenetic groups enable them to coexist. Illustrations and tools to aid students' learning, include case studies, photographs, figures, tables, charts, key concepts and quizlets to self-test. This book is an ideal introduction for students studying primatology, primate behavior or primate ecology"--